(untitled) (International Seven Journal of Health Research, 2024)
The psychological aspects are areas of study with ample importance for the third age and as well as significant improvements in the biological dimensions are told, research point positive effect on the psychological dimensions. Studies suggest that the aged ones if show overwhelming for problems that involve the health. From the moment that the health is reached the concerns in what start it says respect the individuals to become incapable, changedding itself into not motivated individuals and without interests, and of this form reaching them in such a way in the psychological aspect how much in the physical aspect. Methods: One is about a transversal analytical study. The sample was formed by 23 women and 7 healthful sedentary men, who had been submitted to a program of training of force of inferior and superior members and flexibility (emphasis in the flexibility of the trunk). For the evaluation of the depression, a described questionnaire for FIATARONE was used (1996). This instrument consists of 30 related questions the satisfaction with the life and states of spirit of the individual. The total number of negative points was considered, that is, all those answers that are associates the depression feelings. The analysis used statistics to measure the level of significance between daily pay and after-test of the evaluation of the depression was the test of McNemar, that tests given made use in contingency table 2x2, in order to compare ratio of two pairs groups, where the concordant pairs and the opponents in relation are observed the two treatments. Results: The use of the test of McNemar for the comparison enters the collected data in the daily pay-test and after-test program of physical activity, evaluating the depression, demonstrated not to have significant difference in none of the thirty 0 variable that the applied test composes. The study it demonstrated not to collaborate with this psychological state, assuring to be unsatisfactory the point in such a way to present level insignificant for the men how much for the women. This result was observed in both the sorts. Conclusions: The study it demonstrated not to collaborate with this psychological state of depression, being assured to be unsatisfactory the point in such a way to present level of insignificant for the men how much for the women.